RISK FACTORS OF GASTRODUODENAL BLEEDING IN PATIENTS WITH SEVERE BURNS - D. O. Vagner; I. V. Shlyk; V. G. Verbitsky (Вестник хирургии имени И.И. Грекова)
An experience of treatment of 133 patients with severe burns was analyzed. Bleedings from the upper parts of the gastrointestinal tract were diagnosed in 16 patients in different terms since their admission to the hospital. At the moment of carrying out of the endoscopic research all bleedings were considered as taking place. Statistically significant risk factors of the development of gastroduodenal bleedings were considered to be an alcoholic intoxication at the moment of injury and insufficient fluid therapy during the pre-admission stage and young age of the patients. The antisecretory therapy showed that the detection of risk factors in question should be regarded as an indication to the reinforced regime of preventive measures for gastroduodenal injuries.